O dito pelo não dito : uma análise da criminalização secundária das traficantes na cidade do Recife - Castro, Helena Rocha Coutinho de (2016)
This study is based on the analysis of 119 sentencing decisions on drug trafficking cases, all of which involved women as the accused and were rendered within the jurisdiction of Recife throughout 2014. The primary aim of this thesis is to understand the ramifications of gender discourses in relation to women, starting from the hypothesis that (pre)conceptions of a patriarchal and a sexist nature are reproduced in sentencing decisions. Considering that the Judiciary is a key power agency of the criminal justice system, the assumption here is that the message conveyed in those decisions plays an important role in building a social punitive culture. Both critical criminology and a sociology of the administration of justice appeared as the most appropriate theoretical backgrounds in which to locate this work, as they help emphasising the judge's political function and the unfair nature of the criminal justice system’s selection criteria. The research was divided into two phases: a quantitative stage, in which the aim was to learn about the workings of the criminal justice system from the numbers provided by the decisions; and a qualitative stage, based on the content analysis of these decisions. It was found that, in this type of crime, abusive practices perpetrated by the police are commonplace, as most cases involve unlawful flagrant arrests, with the police entering the accused’s home without a warrant and without having to justify his conduct later on in the proceedings. Moreover, the police officer’s version of the facts ends up playing a crucial role in the conviction of the accused, as other evidence is rarely found. Several other pitfalls of the Brazilian criminal system were also identified, such as procedural delays and excessive pre-trial detentions. The research hypothesis was only partially confirmed though, given that nothing positive came out of the sexist dichotomy "victim/witch", as the women were judged not only for drug trafficking crimes, but also for being a mother or a prostitute, and for their behaviour inside and outside their households. On the other hand, the intense police action revealed a high degree of invisibility experienced by these women, who are not receiving any form of protection against possible abuses, including sexual abuse, which puts into question the initial assumption of this research.